Phase Control in Parallel Channels of Shock-Excited Microwave Nanosecond Oscillators; IEEE Transactions on Plasma Science; Vol. 41, iss., 10, pt. 1 - Rostov V. V. Vladislav Vladimirovich; El'chaninov A. A. Anton Aleksandrovich; Klimov A. I. Aleksey Ivanovich; Konev V. Yu. Vladimir Yurievich; Romanchenko I. V. Ilya Viktorovich; Sharypov K. A. Konstantin Anatolyevich; Shunailov S. A. Sergei Afanasievich; Ul'maskulov M. R. Marat Rakhmetovich; Yalandin M. I. Michael Ivanovich (2013, 2013)
Title screen